Estudio de prefactibilidad sobre la instalación de una empresa que brinde el servicio de logística integral para empresas agroexportadoras - Muths Zevallos, Francois Christian Patrick (2019)
The present work includes the study of the feasibility and viability of the installation of a company that provides the logistic and refrigeration service to three fresh agricultural products chosen keeping the cold chain in all the stages that must pass before being exported to compete in the international market.